(untitled) (Iraqi Journal of Medical Sciences, 2017)
Background:The harmful effect of manganese chloride on postnatal spermatogenesis was evidently concluded in previous experimental researches, however, the molecular changes related to this effect of manganese chloride needs further elaboration. Objective:To investigate the toxic effect of prenatal manganese chloride exposure on adult mice testes using malondialdehyde (MDA) antibodies as an immunohistochemical marker. Methods: In this study, 30 pregnant mice were divided into control and experimental groups. The experimental animals were given 0.1 ml of manganese chloride solution (8000 mg/Liter concentration) orally during the first 17 days of pregnancy. The control group of pregnant mice was given 0.1 ml of distilled water orally rather than the solution of manganese chloride. Paraffin sections of the offspring mice testes were stained for general histological features and for anti-MDA immunohistochemical evaluation. The Aperio Image Scope v.9 software was used to evaluate the immunohistochemical reaction. Results: Sections of testes from mice of the experimental group showed distorted morphology and organization of the stages of sperm development with distorted histological criteria of the interstitial tissue. Results from mice testes revealed statistically significant variability of anti-malondialdehyde (MDA) immunohistochemical expression in the experimental group compared to that of the control group. Conclusion: Manganese chloride induced lipid peroxidation as part of its toxic effect. This lipid peroxidation caused cellular injury leading to apoptosis and autophagy. Keywords: Testes, development, manganese chloride, mice, toxicity, immnuohistochemistry, apoptosis Citation: Hayder J. Mubarak, Nameer F. Gaeab, Hussein A. Jarullah. Immunohistochemical malondialdehyde antibodies changes of the adult mice testes affected by prenatal manganese chloride exposure. Iraqi JMS. 2017; Vol. 15(1): 13-19. doi: 10.22578/IJMS.15.1.3